Intellectual capital management practices in Malaysian private hospitals - Noradiva Hamzah,; Hazlina Hassan,; Norman Mohd Saleh,; Amrizah Kamaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Intellectual capital has emerged as an indispensable element for enhancing productivity and sustaining performance of organizations in this knowledge-based economy. In the healthcare industry, intellectual capital forms the basis for continuing innovation and subsequent performance. Hence, the management of hospitals needs sound intellectual capitalmanagement in order to ensure sustainability. Moreover, the activities of hospitals generally depend more on intangible resources such as clinical skills, knowledge, expertise, experiences, competencies, doctor-patient relation, doctors’ and hospital’s reputation rather than physical resources like physical assets. For this study, Malaysian private hospitals were selected as sample to investigate how hospitals extract the value of their intangible capital. This study aims at providing empirical evidence on the intellectual capital management practices in Malaysian private hospitals. Data was collected from a series of interviews with representatives from five private hospitals in Malaysia. Cross-case study analysis was carried out in analysing the data collected to develop patterns found in the evidence. The study reveals that the intellectualcapital management in hospital industry is quite unique especially in the human capital management and the relational capital management. For human capital management, clinical staffs’ competencies are crucial. Interestingly, the study found that physicians are often not the direct employees of the hospitals. This leads to a unique relationship between the hospital and the physicians. Meanwhile for the relational capital management, this study also reveals that the unique relationship that exists between the physicians and patients leads to the structural capital of the hospitals which may influence the hospitals’ reputations and good names.